2018
DOI: 10.1111/ijlh.12849
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the qLabs international normalized ratio point‐of‐care device for monitoring of patients attending an anticoagulation clinic

Abstract: In conclusion, the qLabs POC device is accurate and precise with high levels of dosage concordance and clinical agreement for INR values within and below the target range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…At least two different point-of-care (POC) INR monitors have been validated in South African patients, [89][90][91] and there have been reports of using POC INR monitors in ACCs in Namibia, [19] Kenya, [7,70,92,93] and Nigeria. [87] Considering only the cost per test, POC testing is more expensive than laboratory monitoring; however, it may be cost-effective in some settings.…”
Section: Challenges Accessing Anticoagulationmentioning
confidence: 99%
“…At least two different point-of-care (POC) INR monitors have been validated in South African patients, [89][90][91] and there have been reports of using POC INR monitors in ACCs in Namibia, [19] Kenya, [7,70,92,93] and Nigeria. [87] Considering only the cost per test, POC testing is more expensive than laboratory monitoring; however, it may be cost-effective in some settings.…”
Section: Challenges Accessing Anticoagulationmentioning
confidence: 99%
“…[30][31][32] With a lack of superiority of TEG and ROTEM over standard coagulation tests, POC versions of INR are being developed and studied in other patient populations, such as home warfarin monitoring in the case of POC-INR. 52 Prior studies in patients on cardiopulmonary bypass have shown concordance between near-patient PT/INR testing and central laboratory results, whereas near-patient aPTT testing was discordant. 40,53…”
Section: Discussionmentioning
confidence: 95%
“…At least two different point-of-care INR monitors have been validated in South African patients, [89][90][91] and there have been reports…”
Section: Changing Life Expectancy and Disease Burdenmentioning
confidence: 99%
“…At least two different point‐of‐care INR monitors have been validated in South African patients, 89 , 90 , 91 and there have been reports of using point‐of‐care INR monitors in anticoagulation clinics in Namibia, 19 Kenya 7 , 70 , 92 , 93 and Nigeria. 87 Considering only the cost per test, point‐of‐care testing is more expensive than laboratory monitoring; however, it may be cost‐effective in some settings, for example rural and remote settings.…”
Section: Challenges Accessing Anticoagulationmentioning
confidence: 99%